Emotional prosody recognition is impaired in Alzheimer's disease - Amlerova, Jana; Laczó, Jan; Nedelska, Zuzana; Laczó, Martina; Vyhnálek, Martin; Zhang, Bing; Sheardova, Kateřina; Angelucci, Francesco; Andel, Ross; Hort, Jakub (Alzheimer's research & therapy, 2022)
BACKGROUND: The ability to understand emotions is often disturbed in patients with cognitive impairments. Right temporal lobe structures play a crucial role in emotional processing, especially the amygdala, temporal pole (TP), superior temporal sulcus (STS), and anterior cingulate (AC). Those regions are affected in early stages of Alzheimer ́s disease (AD). The aim of our study was to evaluate emotional prosody recognition (EPR) in participants with amnestic mild cognitive impairment (aMCI) due to AD, AD dementia patients, and cognitively healthy controls and to measure volumes or thickness of the brain structures involved in this process. In addition, we correlated EPR score to cognitive impairment as measured by MMSE. The receiver operating characteristic (ROC) analysis was used to assess the ability of EPR tests to differentiate the control group from the aMCI and dementia groups. METHODS: Eighty-nine participants from the Czech Brain Aging Study: 43 aMCI due to AD, 36 AD dementia, and 23 controls, underwent Prosody Emotional Recognition Test. This experimental test included the playback of 25 sentences with neutral meaning each recorded with different emotional prosody (happiness, sadness, fear, disgust, anger). Volume of the amygdala and thickness of the TP, STS, and rostral and caudal parts of AC (RAC and CAC) were measured using FreeSurfer algorithm software. ANCOVA was used to evaluate EPR score differences. ROC analysis was used to assess the ability of EPR test to differentiate the control group from the aMCI and dementia groups. The Pearson's correlation coefficients were calculated to explore relationships between EPR scores, structural brain measures, and MMSE. RESULTS: EPR was lower in the dementia and aMCI groups compared with controls. EPR total score had high sensitivity in distinguishing between not only controls and patients, but also controls and aMCI, controls and dementia, and aMCI and dementia. EPR decreased with disease severity as it correlated with MMSE. There was a significant positive correlation of EPR and thickness of the right TP, STS, and bilateral RAC. CONCLUSIONS: EPR is impaired in AD dementia and aMCI due to AD. These data suggest that the broad range of AD symptoms may include specific deficits in the emotional sphere which further complicate the patient's quality of life.
Keywords: kvalita života; Alzheimer Disease; Emotions; Quality of Life; emoce; Alzheimerova nemoc; Neuropsychological Tests; lidé; Recognition, Psychology; Humans; Cognitive Dysfunction; neuropsychologické testy; kognitivní dysfunkce; rozpoznávání (psychologie)